Adhesive composition and adhesive sheet
Patent Information
- Application Number
- JP2022081262
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-08-06
- Filing Date
- 2022-05-18
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-05-18
AI Technical Summary
Pressure-sensitive adhesives containing styrenic block copolymers face challenges with lower cohesiveness at high temperatures and trade-offs between rough surface adhesion and high-temperature holding power, leading to insufficient performance in maintaining adhesion under extreme conditions and storage stability.
A pressure-sensitive adhesive composition comprising a block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound, combined with a tackifying resin and a softening agent, where the tackifying resin includes natural tackifying resins with a softening point above 80°C and a petroleum-based tackifying resin with an aromatic ring, optimized in content and type to balance adhesion, high-temperature holding power, and storage stability.
The composition achieves both rough surface adhesion and high-temperature holding power while maintaining good storage stability, with adhesive strength to flexible urethane foam and resistance to peeling under high temperatures.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a pressure-sensitive adhesive composition containing a block copolymer (e.g., a styrene-based block copolymer) of a monovinyl-substituted aromatic compound and a conjugated diene compound, and a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer containing the block copolymer. [Background technology]
[0002] Generally, adhesives (also referred to as pressure-sensitive adhesives; the same applies hereinafter) are in a soft solid (viscoelastic) state at temperatures around room temperature and have the property of easily adhering to an adherend when pressure is applied. Utilizing these properties, adhesives are widely used in a variety of industrial fields, from home appliances to automobiles and office automation equipment, as a joining means with good workability and high adhesive reliability. A typical composition of such an adhesive is a composition containing a polymer that exhibits rubber elasticity at room temperature and a tackifying resin. For example, Patent Documents 1 to 3 describe adhesives that contain a styrene-based block copolymer, such as a styrene-isoprene-styrene block copolymer or a styrene-butadiene-styrene block copolymer, and a tackifying resin. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2020-164845 [Patent Document 2] Patent No. 3994510 [Patent Document 3] Patent No. 5864195 Summary of the Invention [Problem to be solved by the invention]
[0004] PSA containing styrene-based block copolymers as described above generally tend to exhibit poorer properties (especially cohesion) at high temperatures compared to their adhesive properties at room temperature. For example, Patent Document 1 attempts to improve adhesive strength at high temperatures by combining a specific styrene-based elastomer with a specific tackifier resin, but does not examine high-temperature holding power. Patent Document 2 evaluates heat-resistant holding power and other properties using a PSA containing a styrene-isoprene-styrene block copolymer (SIS) and a C5 petroleum-based tackifier resin. However, since the softening point of a C5 petroleum-based tackifier resin is generally less than 110°C (Patent Document 2 uses a resin with a softening point of approximately 100°C), it is difficult to obtain sufficient high-temperature holding power. Patent Document 3 also examines only a composition containing a styrene-butadiene-styrene block copolymer (SBS) and a C5 petroleum-based tackifier resin, and, like Patent Document 2, sufficient high-temperature holding power cannot be expected. The compositions proposed in Patent Documents 1 to 3 do not provide sufficient high-temperature holding power, as shown in the comparative examples described below.
[0005] To improve the high-temperature holding power of a styrene-based block copolymer-containing adhesive, a relatively hard adhesive that can maintain cohesive strength even at high temperatures can be designed. However, such adhesives typically have weak tack and tend to have poor adhesion to rough surfaces, for example. In other words, there is a trade-off between rough surface adhesion and high-temperature holding power. Furthermore, some adhesive materials that can improve the adhesive strength and holding power of styrene-based block copolymer-containing adhesives affect storage stability, limiting the selection of adhesive compositions.
[0006] The present invention was made in view of the above circumstances, and aims to provide a pressure-sensitive adhesive composition that can form a pressure-sensitive adhesive that combines rough surface adhesion and high-temperature holding power and has good storage stability. Another related aim is to provide a pressure-sensitive adhesive sheet that has a good balance of rough surface adhesion, high-temperature holding power, and storage stability. [Means for solving the problem]
[0007] According to this specification, a pressure-sensitive adhesive composition is provided that contains a block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound, a tackifier resin, and a softener. In this pressure-sensitive adhesive composition, the tackifier resin includes a natural product-based tackifier resin (A) that has a softening point above 80°C and does not contain an aromatic ring, and a petroleum-based tackifier resin (B) that has a softening point above 100°C and contains an aromatic ring. The content of the tackifier resin (A) is 40 to 120 parts by weight per 100 parts by weight of the block copolymer. The content of the tackifier resin (B) is 5 to 40 parts by weight per 100 parts by weight of the block copolymer. The total amount of the tackifier resins is 60 to 160 parts by weight per 100 parts by weight of the block copolymer. The content of the softener is 5 to 40 parts by weight per 100 parts by weight of the block copolymer. The above-mentioned pressure-sensitive adhesive composition contains a block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound, and can form a pressure-sensitive adhesive that combines rough surface adhesion and high-temperature holding power, and also has good storage stability.
[0008] In some preferred embodiments, the tackifier resin (A) comprises a terpene resin as the tackifier resin (A1) and a rosin-based resin as the tackifier resin (A2). By using a combination of a terpene resin and a rosin-based resin as the tackifier resin (A), the effects of the technology disclosed herein are preferably realized.
[0009] In some preferred embodiments, the tackifier resin (A2) comprises a rosin-based resin having a softening point of 150° C. or higher. By using a rosin-based resin with a high softening point as the tackifier resin (A2), better high-temperature holding power can be obtained.
[0010] In some preferred embodiments of the PSA composition, the content of the phenolic tackifier resin is less than 1 part by weight relative to 100 parts by weight of the block copolymer. By limiting the amount of the phenolic tackifier resin used as described above, a PSA having good storage stability and excellent quality stability, such as adhesive properties, can be preferably obtained.
[0011] In some embodiments, a styrene-based block copolymer is preferably used as the block copolymer. The effects of the technology disclosed herein are preferably realized in a PSA containing the styrene-based block copolymer. In particular, the effects of the technology disclosed herein can be suitably exhibited in a PSA containing a styrene-isoprene block copolymer.
[0012] In some preferred embodiments, the styrene content of the styrene block copolymer is 10 to 22 wt %. By setting the styrene content of the styrene block copolymer within this range, it is easy to obtain a pressure-sensitive adhesive that achieves both adhesive strength and high-temperature holding power.
[0013] This specification also provides a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer formed from any of the pressure-sensitive adhesive compositions disclosed herein. The pressure-sensitive adhesive sheet has a structure including a pressure-sensitive adhesive layer containing a block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound, and thus exhibits both rough surface adhesion and high-temperature holding power. Furthermore, the pressure-sensitive adhesive sheet has good storage stability, and therefore exhibits excellent quality stability, such as adhesive properties, even when stored for long periods of time. The PSA sheet provided by this specification includes a PSA sheet having a PSA layer, the PSA layer containing a block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound, a tackifier resin, and a softener, the tackifier resins including a natural product-based tackifier resin (A) having a softening point exceeding 80°C and containing no aromatic ring, and a petroleum-based tackifier resin (B) having a softening point exceeding 100°C and containing an aromatic ring, the content of the tackifier resin (A) being 40 to 120 parts by weight relative to 100 parts by weight of the block copolymer, the content of the tackifier resin (B) being 5 to 40 parts by weight relative to 100 parts by weight of the block copolymer, the total amount of the tackifier resins being 60 to 160 parts by weight relative to 100 parts by weight of the block copolymer, and the content of the softener being 5 to 40 parts by weight relative to 100 parts by weight of the block copolymer.
[0014] The present specification also provides a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer containing a block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound and a tackifying resin, wherein the content of the phenolic tackifying resin in the pressure-sensitive adhesive layer is less than 1 part by weight per 100 parts by weight of the block copolymer. This pressure-sensitive adhesive sheet satisfies the following properties: an adhesive strength to flexible urethane foam of 3 N / 10 mm or more, measured under conditions of 23°C, 50% RH, a tensile speed of 300 mm / min, and a peel angle of 180°; and no drop in a holding strength test to a stainless steel plate, measured under conditions of a temperature of 70°C, an application area of 10 mm x 30 mm, a load of 500 g, and a holding time of 1 hour.
[0015] Appropriate combinations of the elements described in this specification may also be included within the scope of the invention for which patent protection is sought by this patent application. [Brief explanation of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic cross-sectional view showing the configuration of a pressure-sensitive adhesive sheet (double-sided pressure-sensitive adhesive sheet with a substrate) according to one embodiment. [Figure 2] FIG. 2 is a schematic cross-sectional view showing the configuration of a pressure-sensitive adhesive sheet (substrate-less double-sided pressure-sensitive adhesive sheet) according to another embodiment. [Figure 3] FIG. 2 is a schematic cross-sectional view showing the configuration of a pressure-sensitive adhesive sheet (single-sided pressure-sensitive adhesive sheet with a substrate) according to another embodiment. [Figure 4] FIG. 1 is an explanatory diagram showing a method for a constant load peel test. DETAILED DESCRIPTION OF THE INVENTION
[0017] Preferred embodiments of the present invention will be described below. Matters necessary for carrying out the present invention other than those specifically mentioned in this specification can be understood by those skilled in the art based on the teachings on carrying out the invention described in this specification and the common general technical knowledge at the time of filing. The present invention can be carried out based on the contents disclosed in this specification and the common general technical knowledge in the relevant field. In the following drawings, components and parts having the same function may be denoted by the same reference numerals, and redundant explanations may be omitted or simplified. The embodiments shown in the drawings are schematic in order to clearly explain the present invention, and do not accurately represent the size or scale of the actual product.
[0018] In this specification, the term "pressure-sensitive adhesive" refers to a material that, as described above, is in a soft solid (viscoelastic) state at temperatures around room temperature and has the property of easily adhering to an adherend by pressure. The pressure-sensitive adhesive in the technology disclosed herein can also be understood as the solid content of a pressure-sensitive adhesive composition or a constituent of a pressure-sensitive adhesive layer.
[0019] In this specification, a "block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound" refers to a polymer having at least one segment (hereinafter also referred to as an "A segment") in which a monovinyl-substituted aromatic compound is the main monomer (meaning more than 50% by weight of the copolymerization component; the same applies hereinafter) and at least one segment (hereinafter also referred to as a "B segment") in which a conjugated diene compound is the main monomer. Generally, the glass transition temperature of the A segment is higher than the glass transition temperature of the B segment. Representative structures of such polymers include a triblock copolymer (ABA triblock copolymer) in which an A segment (hard segment) is attached to each end of a B segment (soft segment), and a diblock copolymer (AB diblock copolymer) consisting of one A segment and one B segment.
[0020] In this specification, "styrene-based block copolymer" refers to a polymer having at least one styrene block. The styrene block refers to a segment in which styrene is the main monomer. A segment consisting essentially of styrene is a typical example of the styrene block referred to here. Furthermore, "styrene-isoprene block copolymer" refers to a polymer having at least one styrene block and at least one isoprene block (a segment in which isoprene is the main monomer). Typical examples of styrene-isoprene block copolymers include a copolymer with a triblock structure (triblock copolymer) having styrene blocks (hard segments) on both ends of an isoprene block (soft segment), and a copolymer with a diblock structure (diblock copolymer) consisting of one isoprene block and one styrene block. "Styrene-butadiene block copolymer" refers to a polymer having at least one styrene block and at least one butadiene block (a segment in which butadiene is the main monomer).
[0021] In this specification, the "styrene content" of a styrene-based block copolymer refers to the weight ratio of the styrene component to the total weight of the block copolymer. The styrene content can be measured by NMR (nuclear magnetic resonance spectroscopy). The proportion of diblock units in a styrene-based block copolymer (hereinafter sometimes referred to as the "diblock unit ratio" or "diblock ratio") is determined by the following method. Specifically, the styrene-based block copolymer is dissolved in tetrahydrofuran (THF), and high-performance liquid chromatography is performed using two liquid chromatography columns, each manufactured by Tosoh Corporation (GS5000H and G4000H), connected in series (a total of four columns, two columns each), at a temperature of 40°C and a flow rate of 1 mL / min, using THF as the mobile phase. The peak area corresponding to the diblock unit is measured from the resulting chart. The diblock unit ratio is then determined by calculating the percentage of the peak area corresponding to the diblock unit relative to the total peak area.
[0022] In this specification, "weight" may be read as "mass." For example, "% by weight" may be read as "% by mass," and "parts by weight" may be read as "parts by mass."
[0023] <Adhesive composition> (Block copolymer of monovinyl-substituted aromatic compound and conjugated diene compound) The pressure-sensitive adhesive composition disclosed herein contains a block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound. The monovinyl-substituted aromatic compound refers to a compound in which one functional group having a vinyl group is bonded to an aromatic ring. A typical example of the aromatic ring is a benzene ring (which may be a benzene ring substituted with a functional group not having a vinyl group (e.g., an alkyl group)). Specific examples of the monovinyl-substituted aromatic compound include styrene, α-methylstyrene, vinyltoluene, and vinylxylene. Specific examples of the conjugated diene compound include 1,3-butadiene and isoprene. Such block copolymers can be used alone or in combination of two or more.
[0024] The block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound is a component that can be used as the base polymer of a PSA. The "base polymer" of a PSA refers to the main component (i.e., the component that accounts for more than 50% by weight of the rubbery polymer) contained in the PSA (a polymer that exhibits rubber elasticity in a temperature range around room temperature).
[0025] In the block copolymer, the A segment (hard segment) preferably has a copolymerization ratio of the monovinyl-substituted aromatic compound (two or more types may be used in combination) of 70% by weight or more (more preferably 90% by weight or more, and may be substantially 100% by weight). In the block copolymer, the B segment (soft segment) preferably has a copolymerization ratio of the conjugated diene compound (two or more types may be used in combination) of 70% by weight or more (more preferably 90% by weight or more, and may be substantially 100% by weight). Such a block copolymer can realize a pressure-sensitive adhesive sheet with higher performance.
[0026] The block copolymer may be in the form of a diblock copolymer, a triblock copolymer, a radial copolymer, a mixture thereof, or the like. In the triblock copolymer or the radial copolymer, it is preferable that an A segment (e.g., a styrene block) is disposed at the end of the polymer chain. This is because the A segments disposed at the end of the polymer chain tend to gather together to form domains, which form a pseudo-crosslinked structure and improve the cohesion of the PSA. In the technology disclosed herein, from the viewpoint of adhesive strength (peel strength) to an adherend, a block copolymer having a diblock ratio of 30% by weight or more (more preferably 40% by weight or more, even more preferably 50% by weight or more, particularly preferably 60% by weight or more, typically 65% by weight or more) can be preferably used. From the viewpoint of peel strength, a block copolymer having a diblock ratio of 70% by weight or more is particularly preferred. Furthermore, from the viewpoint of cohesion and the like, a block copolymer having a diblock ratio of 90% by weight or less (more preferably 85% by weight or less, for example, 80% by weight or less) can be preferably used. For example, a block copolymer having a diblock ratio of 60 to 85% by weight is preferred, and one having a diblock ratio of 70 to 85% by weight (for example, 70 to 80% by weight) is more preferred.
[0027] (styrene-based block copolymer) In some embodiments, the block copolymer is a styrene-based block copolymer. For example, preferred embodiments include the block copolymer containing at least one of a styrene-isoprene block copolymer and a styrene-butadiene block copolymer. The styrene-based block copolymer may contain a hydrogenated product in which at least a portion of the copolymer is hydrogenated (hydrogen atoms are added). The styrene-based block copolymers may be used singly or in combination of two or more. Of the styrene-based block copolymers contained in the PSA, it is preferred that the proportion of styrene-isoprene block copolymer is 70% by weight or more, the proportion of styrene-butadiene block copolymer is 70% by weight or more, or the combined proportion of the styrene-isoprene block copolymer and the styrene-butadiene block copolymer is 70% by weight or more. In some preferred embodiments, substantially all (e.g., 95 to 100% by weight) of the styrene-based block copolymer is a styrene-isoprene block copolymer. In other preferred embodiments, substantially all (e.g., 95 to 100% by weight) of the styrene-based block copolymer is a styrene-butadiene block copolymer. Such a composition allows the effects of applying the technology disclosed herein to be more effectively exhibited.
[0028] The styrene-based block copolymer may be in the form of a diblock copolymer, a triblock copolymer, a radial copolymer, a mixture thereof, or the like. In triblock copolymers and radial copolymers, it is preferable that the styrene block is located at the end of the polymer chain. This is because the styrene blocks located at the end of the polymer chain tend to aggregate to form styrene domains, which form a pseudo-crosslinked structure and improve the cohesion of the PSA. In the technology disclosed herein, from the viewpoint of adhesive strength (peel strength) to an adherend, a styrene-based block copolymer having a diblock ratio of 30% by weight or more (more preferably 40% by weight or more, even more preferably 50% by weight or more, particularly preferably 60% by weight or more, typically 65% by weight or more) can be preferably used. The styrene-based block copolymer may have a diblock ratio of 70% by weight or more (e.g., 75% by weight or more). Furthermore, from the viewpoint of cohesion, etc., a styrene-based block copolymer having a diblock ratio of 90% by weight or less (more preferably 85% by weight or less, e.g., 80% by weight or less) can be preferably used. From the viewpoint of achieving a good balance between rough surface adhesion and high temperature retention by applying the technology disclosed herein, a styrene-based block copolymer with a diblock ratio of 60 to 85% by weight is preferred, and a styrene-based block copolymer with a diblock ratio of 70 to 85% by weight (e.g., 70 to 80% by weight) is more preferred.
[0029] The styrene content of the styrene-based block copolymer may be, for example, 5 to 40% by weight. From the viewpoint of cohesion, a styrene-based block copolymer having a styrene content of 10% by weight or more (more preferably more than 10% by weight, e.g., 12% by weight or more) is usually preferred. From the viewpoint of peel strength, the styrene content is preferably 35% by weight or less (typically 30% by weight or less, more preferably 25% by weight or less), and particularly preferably 22% by weight or less (typically less than 20% by weight, e.g., 18% by weight or less). From the viewpoint of better demonstrating the effect of applying the technology disclosed herein (the effect of achieving both rough surface adhesion and high-temperature holding power), a styrene-based block copolymer having a styrene content of 10 to 22% by weight can be preferably used.
[0030] (tackifying resin) The PSA composition disclosed herein contains a tackifier resin in addition to the block copolymer. Two or more types of tackifier resins can be used in combination. The tackifier resin is not particularly limited, and for example, either a petroleum-based tackifier resin or a natural product-based tackifier resin can be used. The petroleum-based tackifier resin is a compound derived from a petroleum resource, has a chemical structure derived from a petroleum resource, and imparts adhesive properties due to its compatibility with PSA and chemical properties based on the chemical structure. The natural product-based tackifier resin is a compound containing components derived from natural products, has a chemical structure derived from natural products, and imparts adhesive properties due to its compatibility with PSA and chemical properties based on the chemical structure. The technology disclosed herein appropriately selects one or more petroleum-based tackifier resins and natural product-based tackifier resins based on their chemical structures to design a PSA with a good balance of rough surface adhesion, high-temperature retention, and storage stability.
[0031] Examples of petroleum-based tackifying resins include aliphatic (C5) petroleum resins, aromatic (C9) petroleum resins, aliphatic / aromatic copolymer (C5 / C9) petroleum resins, styrene-based resins, and hydrogenated versions of these (e.g., alicyclic petroleum resins obtained by hydrogenating aromatic petroleum resins). Other examples of petroleum-based tackifying resins include coumarone-indene resins and dicyclopentadiene resins. Petroleum-based tackifying resins can be used alone or in combination of two or more.
[0032] Examples of styrene-based resins include those containing a homopolymer of styrene as the main component, those containing a homopolymer of α-methylstyrene as the main component, those containing a homopolymer of vinyltoluene as the main component, and those containing a copolymer containing two or more of styrene, α-methylstyrene, and vinyltoluene as the main component in the monomer composition (for example, an α-methylstyrene / styrene copolymer resin containing an α-methylstyrene / styrene copolymer as the main component).
[0033] The coumarone-indene resin can be a resin containing coumarone and indene as monomer components that make up the resin skeleton (main chain). Other monomer components that can be included in the resin skeleton besides coumarone and indene include styrene, α-methylstyrene, methylindene, vinyltoluene, etc.
[0034] Examples of natural product-based tackifying resins include terpene resins and rosin-based resins. Terpene resins include unmodified terpene resins and modified terpene resins. Rosin-based resins include rosin derivative resins. Natural product-based tackifying resins can be used alone or in combination of two or more.
[0035] Examples of terpene resins (unmodified terpene resins) include α-pinene polymers, β-pinene polymers, dipentene polymers, etc. Examples of modified terpene resins include those obtained by modifying the above-mentioned terpene resins (phenol-modified, aromatic-modified (e.g., styrene-modified), hydrogenation-modified, hydrocarbon-modified, etc.). Specific examples include terpene phenolic resins, aromatic-modified (e.g., styrene-modified) terpene resins, and hydrogenated terpene resins. The above-mentioned terpene phenolic resins may include hydrogenated terpene phenolic resins.
[0036] The above-mentioned "terpene phenol resin" refers to a polymer containing a terpene residue and a phenol residue, and is a concept that encompasses both a copolymer of a terpene and a phenol compound (terpene-phenol copolymer resin) and a phenol-modified terpene homopolymer or copolymer (terpene resin, typically an unmodified terpene resin) modified with phenol.
[0037] Specific examples of rosin-based resins include unmodified rosins (raw rosins) such as gum rosin, wood rosin, and tall oil rosin; modified rosins (hydrogenated rosin, disproportionated rosin, polymerized rosin, other chemically modified rosins, etc.) obtained by modifying these unmodified rosins through hydrogenation, disproportionation, polymerization, etc.; etc. Examples of rosin derivative resins include rosin esters such as those obtained by esterifying unmodified rosin with alcohols (i.e., esterified rosin), and those obtained by esterifying modified rosin (hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.) with alcohols (i.e., esterified modified rosin); unsaturated fatty acid modified rosins obtained by modifying unmodified rosin or modified rosin (hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.) with unsaturated fatty acid; and unsaturated fatty acid modified rosins obtained by modifying rosin esters with unsaturated fatty acid. Examples include rosin esters; rosin alcohols obtained by reducing the carboxyl groups of unmodified rosin, modified rosin (hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.), unsaturated fatty acid modified rosins, or unsaturated fatty acid modified rosin esters; metal salts of rosins (particularly rosin esters) such as unmodified rosin, modified rosin, and various rosin derivatives; and rosin phenolic resins obtained by adding phenol to rosins (unmodified rosin, modified rosin, various rosin derivatives, etc.) using an acid catalyst and then thermally polymerizing the resulting mixture.
[0038] The softening point of the tackifier resin used in the technology disclosed herein is typically higher than 40°C, and may be 60°C or higher. In some embodiments, the softening point of the tackifier resin is 80°C or higher (e.g., greater than 80°C), and preferably 100°C or higher (e.g., greater than 100°C). The upper limit of the softening point of the tackifier resin is not particularly limited, and is typically 200°C or lower. From the viewpoint of rough surface adhesion, etc., the upper limit is preferably 180°C or lower, more preferably 170°C or lower (e.g., 160°C or lower), and may be 140°C or lower, or 120°C or lower.
[0039] In this specification, the softening point of a tackifying resin is defined as a value measured using the softening point test method (ring and ball method) specified in JIS K5902 and JIS K2207. Specifically, the sample is melted as quickly as possible at the lowest possible temperature and carefully filled into a ring placed on a flat metal plate, avoiding the formation of bubbles. After cooling, any raised portion of the ring, including the top edge, is cut off using a slightly heated knife. Next, a holder (ring stand) is placed in a glass container (heating bath) with a diameter of at least 85 mm and a height of at least 127 mm, and glycerin is poured in to a depth of at least 90 mm. Next, a steel ball (9.5 mm diameter, 3.5 g weight) and the ring filled with the sample are immersed in the glycerin without touching each other, and the glycerin temperature is maintained at 20°C ± 5°C for 15 minutes. Next, the steel ball is placed in the center of the surface of the sample in the ring and placed in its fixed position on the holder. Next, keeping the distance from the top of the ring to the glycerin surface at 50 mm, place a thermometer, and heat the container with the center of the thermometer's mercury bulb at the same height as the center of the ring. The flame of the Bunsen burner used for heating should be aimed halfway between the center of the bottom and the edge of the container, and heating should be uniform. After heating begins and the temperature reaches 40°C, the rate of increase in the bath temperature must be 5.0 ± 0.5°C per minute. The sample gradually softens and flows down the ring, and the temperature is read when it finally touches the bottom plate; this is the softening point. The softening point should be measured for two or more samples at the same time, and the average value should be used.
[0040] (Natural tackifying resin (A)) In some embodiments, a natural product-based tackifier resin (A) having a softening point exceeding 80°C and containing no aromatic ring is used as the tackifier resin. Natural product-based tackifier resins having a softening point exceeding 80°C and a molecular structure containing no aromatic ring are highly compatible with PSA containing the block copolymer, and the effects of adding them can be suitably exhibited. By using the natural product-based tackifier resin (A), for example, sufficient high-temperature retention is likely to be obtained based on its softening point. Furthermore, by using a compound containing no aromatic ring, rough surface adhesion tends to be easily obtained and good storage stability is likely to be obtained.
[0041] As the natural product-based tackifying resin (A), any of the above-mentioned natural product-based tackifying resins can be used without particular limitation as long as it has a softening point of over 80°C and a molecular structure that does not contain an aromatic ring. For example, terpene resins, modified terpene resins, rosin-based resins, rosin derivative resins, etc., each having a softening point of over 80°C can be used. The natural product-based tackifying resin (A) can be used alone or in combination of two or more.
[0042] The softening point of the natural product-based tackifier resin (A) is greater than 80°C. From the viewpoint of high-temperature retention, the softening point of the natural product-based tackifier resin (A) is preferably 90°C or higher, more preferably 100°C or higher (e.g., above 100°C), even more preferably 110°C or higher (e.g., above 110°C), and particularly preferably 115°C or higher. In some embodiments, the softening point of the natural product-based tackifier resin (A) may be 120°C or higher, 140°C or higher, or even 150°C or higher. The upper limit of the softening point of the natural product-based tackifier resin (A) is not particularly limited, and is usually appropriately 200°C or lower. From the viewpoint of rough surface adhesion and the like, the upper limit is preferably 180°C or lower, more preferably 170°C or lower (e.g., 160°C or lower), and may be 140°C or lower, or may be 120°C or lower.
[0043] In some preferred embodiments, a terpene resin is used as the natural product-based tackifier resin (A). The terpene resin is highly compatible with the pressure-sensitive adhesive containing the block copolymer, and its addition effect can be favorably exhibited. Although not intended to be particularly limiting, the terpene resin is highly compatible with the soft segment (a segment having a conjugated diene compound as the main monomer) of the block copolymer, and is thought to impart appropriate cohesive strength to the soft segment based on its softening point, thereby contributing to improved high-temperature holding power. For example, by using an appropriate amount of the terpene resin, it is possible to achieve a good balance between rough surface adhesion and high-temperature holding power.
[0044] The softening point of the terpene resin is greater than 80°C, and is not otherwise particularly limited. From the viewpoint of high-temperature retention, the softening point of the terpene resin is preferably 90°C or higher, more preferably 95°C or higher, even more preferably 100°C or higher (e.g., above 100°C), particularly preferably 110°C or higher (e.g., above 110°C), and particularly preferably 115°C or higher. The upper limit of the softening point of the terpene resin is usually 200°C or lower, and from the viewpoint of rough surface adhesion, etc., it is preferably 160°C or lower, more preferably 140°C or lower, and may be 120°C or lower.
[0045] In embodiments in which a terpene resin is used as the natural product-based tackifier resin (A), the content of the terpene resin in the PSA composition may be, for example, 1 part by weight or more, or even 10 parts by weight or more, per 100 parts by weight of the block copolymer. In some preferred embodiments, from the viewpoint of effectively exerting the effects of adding the terpene resin, the content of the terpene resin per 100 parts by weight of the block copolymer is 20 parts by weight or more, or 30 parts by weight or more, or 40 parts by weight or more, or even 50 parts by weight or more. In some embodiments, the content of the terpene resin per 100 parts by weight of the block copolymer is suitably less than 120 parts by weight. From the viewpoint of achieving both rough surface adhesion and high-temperature holding power, the content is preferably 100 parts by weight or less, more preferably 80 parts by weight or less, or may be 70 parts by weight or less, or may be 50 parts by weight or less.
[0046] In embodiments using a terpene resin as the natural product-based tackifier resin (A), the amount of the terpene resin relative to 1 part by weight of the B segment (a segment having a conjugated diene compound as the main monomer) in the block copolymer is, for example, 0.1 parts by weight or more, preferably 0.2 parts by weight or more, and may be 0.4 parts by weight or more, 0.5 parts by weight or more, or even 0.6 parts by weight or more. In some embodiments, the amount of the terpene resin relative to 1 part by weight of the B segment of the block copolymer is suitably 1.5 parts by weight or less. From the viewpoint of achieving both rough surface adhesion and high-temperature retention, the amount is preferably 1.2 parts by weight or less, more preferably 1 part by weight or less, and may be 0.8 parts by weight or less, or even 0.6 parts by weight or less. By using an amount of terpene resin within this range, the effect of adding the terpene resin can be effectively exerted due to the compatibility of the terpene resin with the soft segment.
[0047] In some preferred embodiments, a rosin-based resin is used as the natural product-based tackifier resin (A). The rosin-based resin is highly compatible with the pressure-sensitive adhesive containing the block copolymer, allowing its addition to exhibit its desired effects. While not intended to be limiting, the rosin-based resin typically has high-polarity and low-polarity regions in a single molecule, is compatible with each segment (hard segment and soft segment) of the block copolymer, and is thought to contribute to achieving both rough surface adhesion and high-temperature retention based on a compatibility mechanism different from that of the terpene resin. The use of a rosin-based resin is also advantageous in that it can improve adhesion to polar substrates such as metals.
[0048] The softening point of the rosin resin is greater than 80°C, and is not otherwise particularly limited. From the viewpoint of high-temperature retention, the softening point of the rosin resin is preferably 100°C or higher, more preferably 110°C or higher, even more preferably 130°C or higher, and particularly preferably 150°C or higher. The upper limit of the softening point of the rosin resin is usually 200°C or lower, and from the viewpoint of rough surface adhesion, etc., it is preferably 180°C or lower, and may be 170°C or lower.
[0049] In embodiments in which a rosin-based resin is used as the natural product-based tackifier resin (A), the content of the rosin-based resin in the PSA composition may be, for example, 1 part by weight or more, or even 10 parts by weight or more, per 100 parts by weight of the block copolymer. In some preferred embodiments, from the viewpoint of effectively exerting the effects of adding the rosin-based resin, the content of the rosin-based resin per 100 parts by weight of the block copolymer is 20 parts by weight or more, 30 parts by weight or more, 40 parts by weight or more, or even 50 parts by weight or more. In some embodiments, the content of the rosin-based resin per 100 parts by weight of the block copolymer is suitably 120 parts by weight or less, and from the viewpoint of achieving both rough surface adhesion and high-temperature holding power, the content is preferably 100 parts by weight or less, more preferably 80 parts by weight or less, and may be 70 parts by weight or less, 50 parts by weight or less, or even 30 parts by weight or less.
[0050] In some preferred embodiments, the natural product-based tackifier resin (A) comprises the terpene resin described above as the tackifier resin (A1) and the rosin-based resin described above as the tackifier resin (A2). Using a terpene resin and a rosin-based resin in combination as the tackifier resin (A) can achieve both better rough surface adhesion and high-temperature retention. In embodiments in which the tackifier resin (A1) and the tackifier resin (A2) are used in combination, the ratio of their use is not particularly limited. In some embodiments, the ratio (A1 / A2) of the content of the tackifier resin (A1) to the content of the tackifier resin (A2) is, for example, 1 / 10 or more, or may be 1 / 5 or more, 1 / 3 or more, 1 / 2 or more, 2 / 3 or more, or 1 or more. The ratio (A1 / A2) may be 10 or less, 5 or less, 3 or less, or 2 or less.
[0051] In embodiments using a natural product-based tackifier resin (A), the content of the natural product-based tackifier resin (A) in the PSA composition (the total amount when two or more types are included) is not particularly limited, and an appropriate amount can be selected to achieve the desired effect. In some embodiments, the content of the natural product-based tackifier resin (A) is more than 30 parts by weight and less than 140 parts by weight, or may be 35 to 130 parts by weight, per 100 parts by weight of the block copolymer. In some preferred embodiments, the content of the natural product-based tackifier resin (A) is 40 to 120 parts by weight per 100 parts by weight of the block copolymer. This allows for a well-balanced improvement in rough surface adhesion and high-temperature holding power. The content of the natural product-based tackifier resin (A) per 100 parts by weight of the block copolymer may be 50 parts by weight or more, 70 parts by weight or more, 90 parts by weight or more, or 100 parts by weight or more. Furthermore, the content of the natural product-based tackifier resin (A) relative to 100 parts by weight of the block copolymer is preferably 110 parts by weight or less, and may be 90 parts by weight or less, 80 parts by weight or less, or 60 parts by weight or less.
[0052] (Petroleum-based tackifying resin (B)) In some embodiments, the tackifier resin comprises a petroleum-based tackifier resin (B) having a softening point exceeding 100°C and containing an aromatic ring. Petroleum-based tackifier resins with a softening point exceeding 100°C and a molecular structure containing an aromatic ring are highly compatible with PSA containing the block copolymer, and the effects of their addition can be optimally exhibited. By using the petroleum-based tackifier resin (B), sufficient high-temperature holding power can be easily obtained due to the structure containing an aromatic ring and the softening point. While not intended to be particularly limiting, the petroleum-based tackifier resin (B) has an aromatic ring, and therefore is highly compatible with domains (hereinafter also referred to as "hard domains") formed by the aggregation of hard segments (segments whose main monomer is a monovinyl-substituted aromatic compound) of the block copolymer (e.g., styrene domains in a styrene-based block copolymer). It is believed that the compatibility of the high-softening-point petroleum-based tackifier resin (B) with the hard domains improves the heat resistance of the pseudo-crosslinks formed by the hard domains, contributing to improved high-temperature holding power of the PSA.
[0053] As the petroleum-based tackifying resin (B), any of the above-mentioned petroleum-based tackifying resins can be used without particular limitation as long as it has a softening point exceeding 100°C and a molecular structure containing an aromatic ring. For example, aromatic (C9) petroleum resins, aliphatic / aromatic copolymer (C5 / C9) petroleum resins, styrene-based resins, coumarone-indene resins, etc., all of which have a softening point exceeding 100°C, can be used. Of these, aromatic petroleum resins and styrene-based resins are preferred. The petroleum-based tackifying resin (B) can be used alone or in combination of two or more.
[0054] The softening point of the petroleum-based tackifier resin (B) is greater than 100°C. From the viewpoint of high-temperature retention, the softening point of the petroleum-based tackifier resin (B) is suitably 110°C or higher, preferably 125°C or higher, more preferably 135°C or higher, and even more preferably 150°C or higher. There are no particular limitations on the upper limit of the softening point of the petroleum-based tackifier resin (B), and it is usually suitably 200°C or lower. From the viewpoint of rough surface adhesion and the like, it is preferably 180°C or lower, more preferably 170°C or lower (for example, 160°C or lower), and may be 150°C or lower, or 140°C or lower.
[0055] In embodiments using a petroleum-based tackifier resin (B), the content of the petroleum-based tackifier resin (B) in the PSA composition (the total amount when two or more types are included) is not particularly limited, and an appropriate amount can be selected to achieve the desired effect. In some embodiments, the content of the petroleum-based tackifier resin (B) is greater than 0 parts by weight and less than 50 parts by weight, or 1 to 45 parts by weight, per 100 parts by weight of the block copolymer. In some preferred embodiments, the content of the petroleum-based tackifier resin (B) is 5 to 40 parts by weight per 100 parts by weight of the block copolymer. This allows for a well-balanced improvement in rough surface adhesion and high-temperature holding power. The content of the petroleum-based tackifier resin (B) per 100 parts by weight of the block copolymer may be 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, or 30 parts by weight or more (e.g., 35 parts by weight or more). Furthermore, the content of the petroleum-based tackifying resin (B) relative to 100 parts by weight of the block copolymer may be 35 parts by weight or less, or 25 parts by weight or less, from the viewpoint of rough surface adhesion.
[0056] Although not particularly limited, in embodiments using a petroleum-based tackifier resin (B), the amount of the petroleum-based tackifier resin (B) relative to 1 part by weight of the A segment (a segment having a monovinyl-substituted aromatic compound as the main monomer; in embodiments where the block copolymer is a styrene-based block copolymer, the styrene component) in the block copolymer is, for example, 0.3 parts by weight or more, or may be 0.6 parts by weight or more, 1 part by weight or more, 1.3 parts by weight or more, or 2 parts by weight or more. In some embodiments, the amount of the petroleum-based tackifier resin (B) relative to 1 part by weight of the A segment (e.g., the styrene component) in the block copolymer is suitably 2.7 parts by weight or less, and from the viewpoint of rough surface adhesion, may be 2.4 parts by weight or less, 1.8 parts by weight or less, or 1.5 parts by weight or less. By setting the amount of the petroleum-based tackifying resin (B) within the above range, the petroleum-based tackifying resin (B) is well compatible with domains formed by aggregation of hard segments of the block copolymer (for example, styrene domains in a styrene-based block copolymer), and the effect of adding the petroleum-based tackifying resin (B) can be effectively exerted.
[0057] In some preferred embodiments, the natural product-based tackifier resin (A) and the petroleum-based tackifier resin (B) are used in combination as tackifier resins. By using the natural product-based tackifier resin (A) and the petroleum-based tackifier resin (B) in combination, the difference in their chemical structures acts on the block copolymer, making it easy to form a PSA with good shelf life and a good balance of rough surface adhesion and high-temperature retention. In embodiments where the natural product-based tackifier resin (A) and the petroleum-based tackifier resin (B) are used in combination, the ratio of their use is not particularly limited. In some embodiments, the ratio (A / B) of the content of the natural product-based tackifier resin (A) to the content of the petroleum-based tackifier resin (B) is, for example, 1 or more, preferably 2 or more, or may be 3 or more, 4 or more, 5 or more, or 6 or more, by weight. The ratio (A / B) is, for example, 20 or less, suitably 16 or less, or may be 12 or less, or may be 10 or less.
[0058] (Other tackifying resins) The PSA composition may contain a tackifier resin different from the natural product-based tackifier resin (A) and the petroleum-based tackifier resin (B) to the extent that the effects of the present invention are not impaired. Examples of tackifier resins different from the natural product-based tackifier resin (A) and the petroleum-based tackifier resin (B) include natural product-based tackifier resins with a softening point of 80°C or lower, natural product-based tackifier resins containing an aromatic ring, petroleum-based tackifier resins with a softening point of 100°C or lower, and petroleum-based tackifier resins without an aromatic ring. Examples of natural product-based tackifier resins with an aromatic ring include aromatic-modified terpene resins, terpene phenolic resins, and rosin phenolic resins. Examples of petroleum-based tackifier resins without an aromatic ring include aliphatic (C5) petroleum resins and alicyclic petroleum resins.
[0059] The technology disclosed herein makes it possible to form a PSA that exhibits a good balance of rough surface adhesion, high-temperature retention, and shelf life without relying on tackifier resins other than the natural product-based tackifier resin (A) and the petroleum-based tackifier resin (B) (i.e., without requiring them as essential components). Therefore, it is possible to employ a composition in which the amount of tackifier resins other than the natural product-based tackifier resin (A) and the petroleum-based tackifier resin (B) is limited, or a composition that is substantially free of such tackifier resins. For example, the content of tackifier resins other than the natural product-based tackifier resin (A) and the petroleum-based tackifier resin (B) can be less than 30 wt. %, or even less than 10 wt. %, or even less than 3 wt. The technology disclosed herein can be implemented in a PSA composition that is substantially free of tackifier resins other than the natural product-based tackifier resin (A) and the petroleum-based tackifier resin (B).
[0060] Furthermore, the technology disclosed herein can achieve both rough surface adhesion and high-temperature cohesion without relying on phenolic tackifier resins (e.g., terpene phenolic resins) by using a tackifier resin other than a phenolic tackifier resin and in a suitable amount. While phenolic tackifier resins can contribute to improved adhesive properties, they can also accelerate PSA degradation. Therefore, achieving both rough surface adhesion and high-temperature cohesion without requiring a phenolic tackifier resin as an essential component is also beneficial in terms of achieving excellent shelf life. This configuration allows for the realization of a PSA with desired adhesive properties and long-term quality stability. From this perspective, the content of the phenolic tackifier resin can be less than 30 wt %, or alternatively, less than 10 wt %, or even less than 3 wt %, of the total amount of tackifier resins contained in the PSA composition. The technology disclosed herein can also be implemented in a PSA composition that is substantially free of a phenolic tackifier resin. Furthermore, the content of the phenolic tackifier resin in the PSA composition is preferably less than 30 parts by weight, more preferably less than 10 parts by weight, even more preferably less than 3 parts by weight, and particularly preferably less than 1 part by weight, relative to 100 parts by weight of the block copolymer. By limiting the amount of the phenolic tackifier resin used as described above, a PSA having good storage stability and excellent quality stability, such as adhesive properties, can be preferably obtained. Note that the term "phenolic tackifier resin" as used herein refers to a tackifier resin having a molecular structure containing a phenol skeleton, and is a concept that encompasses terpene phenolic resins, hydrogenated terpene phenolic resins, phenolic resins (such as alkylphenol resins and xylene-formaldehyde resins), rosin phenolic resins, etc.
[0061] (Total amount of tackifier resin) The total amount of tackifier resin in the PSA composition is not particularly limited, and an appropriate amount can be used to achieve the desired effect. In some embodiments, the total amount of tackifier resin is greater than 35 parts by weight and less than 180 parts by weight, or may be 45 to 170 parts by weight, per 100 parts by weight of the block copolymer. In some preferred embodiments, the total amount of tackifier resin is 60 to 160 parts by weight per 100 parts by weight of the block copolymer. This allows for a well-balanced improvement in rough surface adhesion and high-temperature holding power. The total amount of tackifier resin per 100 parts by weight of the block copolymer may be 80 parts by weight or more, 100 parts by weight or more, or 110 parts by weight or more. Furthermore, the total amount of tackifier resin per 100 parts by weight of the block copolymer is preferably 140 parts by weight or less, or may be 130 parts by weight or less, or may be 120 parts by weight or less, or may be 110 parts by weight or less. In some embodiments, the total amount of tackifier resins relative to 100 parts by weight of the block copolymer may be less than 100 parts by weight, less than 90 parts by weight, or less than 80 parts by weight. Even in such a configuration in which the total amount of tackifier resins is limited, the technology disclosed herein can still achieve the desired effects.
[0062] (softener) The PSA composition disclosed herein preferably contains a softener. By incorporating a softener into the PSA, adhesion to the adherend can be improved, and rough surface adhesion can be improved. For example, incorporating a softener into a composition with high high-temperature cohesion can easily form a PSA that combines rough surface adhesion and high-temperature retention. Here, the term "softener" as used herein refers to a fluid that is liquid or viscous at room temperature (e.g., 25°C), or a material with a softening point of 40°C or lower. The softening point can be measured using a method similar to that used to measure the softening point of the tackifier resin described above.
[0063] The type of softener is not particularly limited, and an appropriate one is selected depending on the adhesive composition (the type of block copolymer and the type of tackifying resin), etc. Examples of softeners include liquid rubbers such as polybutene and polyisoprene, and process oils such as paraffinic oil and naphthenic oil. Liquid resins such as liquid terpene resins and liquid rosin resins may also be used as softeners. Other examples of softeners include esters of higher fatty acids (higher fatty acid esters) such as stearic acid and palmitic acid, and fatty acid amides. Of these, liquid terpene resins and process oils are preferably used. Softeners can be used alone or in combination of two or more.
[0064] The content of the softener in the PSA composition is not particularly limited, and an appropriate amount can be adopted to achieve the desired effect. In some embodiments, the content of the softener is greater than 0 parts by weight and less than 50 parts by weight, or may be 1 to 45 parts by weight, per 100 parts by weight of the block copolymer. In some preferred embodiments, the content of the softener is 5 to 40 parts by weight per 100 parts by weight of the block copolymer. This facilitates the formation of a PSA with a well-balanced improved rough surface adhesion and high-temperature holding power. The content of the softener per 100 parts by weight of the block copolymer may be 10 parts by weight or more, 15 parts by weight or more, or 20 parts by weight or more. Furthermore, the content of the softener per 100 parts by weight of the block copolymer may be 35 parts by weight or less, or may be 30 parts by weight or less.
[0065] (Isocyanate compounds) The pressure-sensitive adhesive composition disclosed herein may further contain an isocyanate compound. The use of an isocyanate compound can improve the cohesive strength of the pressure-sensitive adhesive. A preferred isocyanate compound is a polyfunctional isocyanate (a compound having an average of two or more isocyanate groups per molecule, including those having an isocyanurate structure). One or more polyfunctional isocyanates selected from various isocyanate compounds (polyisocyanates) having two or more isocyanate groups per molecule can be used as the polyfunctional isocyanate. Examples of such polyfunctional isocyanates include aliphatic polyisocyanates, alicyclic polyisocyanates, and aromatic polyisocyanates.
[0066] When an isocyanate compound is used, its amount is not particularly limited, but can be, for example, more than 0 part by weight and up to 10 parts by weight (typically 0.01 to 10 parts by weight) per 100 parts by weight of the block copolymer. Typically, the amount of isocyanate compound used per 100 parts by weight of the block copolymer is 0.1 to 10 parts by weight, preferably 0.1 to 5 parts by weight (typically 0.3 to 3 parts by weight, e.g., 0.5 to 1 part by weight). In some embodiments, the pressure-sensitive adhesive composition may be substantially free of an isocyanate compound. The technology disclosed herein can improve high-temperature holding power and constant-load peel properties without using an isocyanate compound. The term "substantially free of an isocyanate compound" refers to a pressure-sensitive adhesive composition containing less than 0.1% by weight (e.g., 0 to 0.05% by weight) of an isocyanate compound.
[0067] (anti-aging agent) The adhesive composition disclosed herein may contain an antioxidant, if necessary. The use of an antioxidant can improve the quality stability of the adhesive. Antiaging agents may be used alone or in combination of two or more. Examples of antioxidants include phosphorus-based antioxidants, phenol-based antioxidants (e.g., hindered phenol-based antioxidants), hindered amine-based antioxidants, aromatic amine-based antioxidants, and sulfur-based antioxidants. While not particularly limited, the amount of antioxidant contained in the adhesive composition disclosed herein may be, for example, approximately 20 parts by weight or less, typically 10 parts by weight or less, and may even be 5 parts by weight or less, per 100 parts by weight of the block copolymer. Furthermore, the amount of antioxidant may be, for example, 0.1 parts by weight or more, or may even be 0.5 parts by weight or more, or may even be 1 part by weight or more, per 100 parts by weight of the block copolymer.
[0068] (Other ingredients) The pressure-sensitive adhesive composition disclosed herein may contain various additives commonly used in the field of pressure-sensitive adhesives, such as leveling agents, crosslinking agents, crosslinking aids, plasticizers, fillers, colorants (pigments, dyes, etc.), antistatic agents, UV absorbers, and light stabilizers, as needed. Conventionally known additives can be used in the usual manner. The pressure-sensitive adhesive composition disclosed herein may also contain one or more rubbery polymers other than the block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound, to the extent that the effects of the present invention are not impaired. The technology disclosed herein can be preferably implemented in an embodiment in which the pressure-sensitive adhesive composition is substantially free of rubbery polymers other than the block copolymer (e.g., an embodiment in which the content is 0 to 1 part by weight per 100 parts by weight of the block copolymer).
[0069] In some embodiments, the pressure-sensitive adhesive composition may be substantially free of a chelate compound. Here, the chelate compound refers to, for example, a chelate compound of an alkaline earth metal oxide and a resin (such as an alkylphenol resin) having a functional group (such as a hydroxyl group or a methylol group) to which the oxide can be coordinated. The technology disclosed herein can be preferably implemented in an embodiment in which the pressure-sensitive adhesive composition does not contain any such chelate compound or the chelate compound content is 1 wt % or less. According to this embodiment, a pressure-sensitive adhesive sheet with superior adhesive strength can be achieved.
[0070] In some preferred embodiments, the PSA composition may be a composition in which the total amount of the block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound, the tackifier resin, and the softener accounts for 90 wt % or more of the total weight of the PSA (i.e., the weight of the PSA layer constituted by this PSA). For example, a preferred embodiment may be one in which the total amount is 90 to 99.8 wt % (typically, for example, 95 to 99.5 wt %) of the total weight of the PSA.
[0071] The form of the PSA composition disclosed herein is not particularly limited, and may be, for example, a solvent-based PSA composition containing a PSA (adhesive component) having the above-described composition in an organic solvent, a water-dispersed PSA composition, typically an aqueous emulsion PSA composition, or a hot-melt PSA composition. From the viewpoints of coatability and freedom of substrate selection, solvent-based or water-dispersed PSA compositions are preferably used. From the viewpoint of achieving higher adhesive performance, solvent-based PSA compositions are particularly preferred. Furthermore, hot-melt PSA compositions are preferred from the viewpoints of productivity and reducing environmental impact, since they can be applied in a heated, molten state that is substantially free of organic solvents.
[0072] The solvent-based pressure-sensitive adhesive composition is typically prepared in the form of a solution containing the above-mentioned components in an organic solvent. The organic solvent can be appropriately selected from known or commonly used organic solvents. For example, any one solvent or a mixture of two or more solvents selected from aromatic compounds (typically aromatic hydrocarbons) such as toluene and xylene; acetate esters such as ethyl acetate and butyl acetate; aliphatic or alicyclic hydrocarbons such as hexane, cyclohexane, and methylcyclohexane; halogenated alkanes such as 1,2-dichloroethane; and ketones such as methyl ethyl ketone and acetylacetone can be used. Although not particularly limited, it is usually appropriate to prepare the solvent-based pressure-sensitive adhesive composition so that the nonvolatile content (NV) is 30 to 65 wt % (e.g., 40 to 55 wt %).
[0073] Various conventionally known methods can be used to obtain a pressure-sensitive adhesive sheet from the pressure-sensitive adhesive composition. For example, a method (direct method) in which the pressure-sensitive adhesive composition is directly applied (typically coated) to a substrate and dried to form a pressure-sensitive adhesive layer can be preferably used. Alternatively, the pressure-sensitive adhesive composition can be applied to a surface with good releasability (for example, the surface of a release liner, the back surface of a release-treated support substrate, etc.) and dried to form a pressure-sensitive adhesive layer on the surface. Furthermore, a method (transfer method) in which the formed pressure-sensitive adhesive layer is transferred to a substrate can also be used. The pressure-sensitive adhesive composition can be applied using a known or conventional coater, such as a gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, bar coater, knife coater, or spray coater. From the viewpoints of accelerating the crosslinking reaction and improving production efficiency, the pressure-sensitive adhesive composition is preferably dried under heating. Typically, a drying temperature of, for example, about 40°C to 150°C (typically 40°C to 120°C, e.g., 50°C to 120°C, or even 70°C to 100°C) can be preferably used. The drying time is not particularly limited, but may be from several tens of seconds to several minutes (e.g., approximately 5 minutes or less, preferably 30 seconds to 2 minutes). An additional drying step may be performed thereafter, if necessary. The pressure-sensitive adhesive layer is typically formed continuously, but may be formed in a regular or random pattern, such as dots or stripes, depending on the purpose and application.
[0074] (Adhesive layer thickness) Although not particularly limited, the thickness of the pressure-sensitive adhesive layer is suitably about 4 μm or more (e.g., 20 μm or more), and about 150 μm or less (typically 120 μm or less, e.g., 100 μm or less). In some embodiments, the thickness of the pressure-sensitive adhesive layer may be preferably 30 μm or more, more preferably 40 μm or more, and even more preferably 50 μm or more (e.g., 60 μm or more). A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer of such a thickness can exhibit excellent adhesive performance (typically, both rough surface adhesion and high-temperature holding power). In the case of a double-sided pressure-sensitive adhesive sheet with a substrate, it is preferable to configure the substrate so that a pressure-sensitive adhesive layer of the above thickness is provided on each side of the substrate. The thicknesses of the pressure-sensitive adhesive layers may be the same or different.
[0075] <Adhesive sheet structure example> The PSA sheet disclosed herein (which may be in a long form such as a tape) may be in the form of, for example, a double-sided PSA sheet having the cross-sectional structure shown in FIG. 1 . This double-sided PSA sheet 1 comprises a substrate (e.g., a plastic film) 15 and a first PSA layer 11 and a second PSA layer 12 supported on both sides of the substrate 15. More specifically, the first PSA layer 11 and the second PSA layer 12 are provided on a first side 15A and a second side 15B (both of which are non-releasable), respectively, of the substrate 15. Before use (before attachment to an adherend), the double-sided PSA sheet 1 may be in a spirally wound form, as shown in FIG. 1 , superimposed on a release liner 21, both of whose front and back surfaces 21A and 21B are release surfaces. In this form of double-sided PSA sheet 1, the surface of the second PSA layer 12 (second adhesive surface 12A) is protected by the front side 21A of the release liner 21, and the surface of the first PSA layer 11 (first adhesive surface 11A) is protected by the back side 21B of the release liner 21. Alternatively, the first adhesive surface 11A and the second adhesive surface 12A may be protected by two independent release liners, respectively.
[0076] The technology disclosed herein is preferably applied to a substrate-attached double-sided PSA sheet as shown in Fig. 1, but can also be applied to a substrate-less (i.e., substrateless) double-sided PSA sheet 2 as shown in Fig. 2. Before use, the double-sided PSA sheet 2 may be in a form in which the first adhesive surface 11A and the second adhesive surface 11B of the substrate-less PSA layer 11 are protected by release liners 21, 22, at least the surface (front surface) of which faces the PSA layer, serving as a release surface. Alternatively, the release liner 22 may be omitted, and a release liner 21 having release surfaces on both sides may be used, which is then superimposed on the PSA layer 11 and wound spirally, so that the second adhesive surface 11B abuts against the back surface of the release liner 21 and is protected.
[0077] The technology disclosed herein may also be applied to a single-sided adhesive substrate-attached PSA sheet 3 comprising a substrate 15 and a PSA layer 11 supported on a first surface (non-release surface) 15A of the substrate, as shown in Figure 3. Before use, the PSA sheet 3 may be in a form in which the surface (adhesive surface) 11A of the PSA layer 11 is protected by a release liner 21, at least the surface (front surface) on the PSA layer side, is a release surface, as shown in Figure 3. Alternatively, the release liner 21 may be omitted, and a substrate 15 having a second surface 15B as a release surface may be used, and the substrate-attached PSA sheet 3 may be rolled up so that the first adhesive surface 11A is protected by being in contact with the second surface 15B of the substrate 15.
[0078] <Base material> When the technology disclosed herein is applied to a substrate-attached double-sided PSA sheet or a substrate-attached single-sided PSA sheet, the substrate can be selected appropriately depending on the intended use of the PSA sheet, and can be, for example, a plastic film such as polypropylene film, ethylene-propylene copolymer film, polyester film, or polyvinyl chloride film; a foam sheet made of a foam such as polyurethane foam, polyethylene foam, or polychloroprene foam; a woven fabric or nonwoven fabric (including paper such as Japanese paper or wood-free paper) made by spinning various fibrous materials (natural fibers such as hemp or cotton, synthetic fibers such as polyester or vinylon, or semi-synthetic fibers such as acetate, etc.); or a metal foil such as aluminum foil or copper foil. The plastic film (typically a non-porous plastic film, distinct from woven fabric or nonwoven fabric) can be either a non-stretched film or a stretched (uniaxially or biaxially stretched) film. Furthermore, the surface of the substrate on which the PSA layer is to be formed may be subjected to a surface treatment such as a primer coating or corona discharge treatment.
[0079] Examples of nonwoven fabrics used as the substrate include nonwoven fabrics made from natural fibers such as pulps such as wood pulp, cotton, and hemp; nonwoven fabrics made from chemical fibers (synthetic fibers) such as polyester fibers such as polyethylene terephthalate (PET) fibers, rayon, vinylon, acetate fibers, polyvinyl alcohol (PVA) fibers, polyamide fibers, polyolefin fibers, and polyurethane fibers; and nonwoven fabrics made from a combination of two or more fibers of different materials. Among these, nonwoven fabrics made from pulp or hemp (e.g., hemp pulp) and nonwoven fabrics made from PET fibers are preferred from the standpoint of adhesive impregnation and repulsion resistance. The use of a nonwoven fabric substrate also contributes to improving the flexibility and ease of hand-tearing of the adhesive sheet.
[0080] The nonwoven fabric (nonwoven fabric substrate) has a basis weight of approximately 30 g / m 2 or less (e.g. 25g / m 2 Below 20 g / m, typically 2 A nonwoven fabric having such a basis weight is suitable for producing a lightweight PSA sheet with excellent adhesive performance. From the viewpoint of repulsion resistance, a basis weight of 18 g / m 2 Less than (e.g. 16g / m 2 Below 15g / m, typically 2 From the viewpoint of improving the strength of the substrate itself, the above-mentioned basis weight is 10 g / m 2 or more (e.g., 12 g / m 2 or more, typically 13 g / m 2 or more).
[0081] The bulk density of the nonwoven fabric substrate (which can be calculated by dividing the basis weight by the thickness) is approximately 0.20 g / cm 3 The above is appropriate, and 0.25g / cm 3 or more (e.g., 0.30 g / cm 3 or more) and approximately 0.50 g / cm 3 The following is appropriate: 0.40 g / cm 3 or less (e.g., 0.35 g / cm 3When the bulk density is within the above range, the substrate itself has an appropriate strength and good adhesive impregnation is obtained. From the viewpoint of repulsion resistance, a bulk density of 0.25 to 0.40 g / cm is preferable. 3 (e.g. 0.30-0.35g / cm 3 ) is particularly preferred.
[0082] In addition to the constituent fibers described above, the nonwoven fabric substrate may contain resin components such as starch (e.g., cationized starch), polyacrylamide, viscose, polyvinyl alcohol, urea-formaldehyde resin, melamine-formaldehyde resin, and polyamide-polyamine epichlorohydrin. The resin components may function as paper strength agents for the nonwoven fabric substrate. The strength of the nonwoven fabric substrate can be adjusted by using such resin components as needed. The nonwoven fabric substrate may also contain additives commonly used in the field of nonwoven fabric manufacturing, such as retention aids, drainage aids, viscosity modifiers, and dispersants, as needed.
[0083] The thickness of the substrate can be selected appropriately depending on the purpose, but is generally suitably about 2 μm or more (typically 10 μm or more), and preferably 500 μm or less (typically 200 μm or less). When a nonwoven fabric is used as the substrate, the thickness of the nonwoven fabric substrate is suitably about 150 μm or less. From the viewpoint of sufficiently impregnating the entire substrate with the adhesive, the thickness is preferably 100 μm or less (e.g., 70 μm or less). Furthermore, taking into consideration handleability during the production of the adhesive sheet, the thickness is preferably 10 μm or more (e.g., 25 μm or more). From the viewpoint of repulsion resistance, the thickness is preferably 30 μm or more (e.g., 35 μm or more, typically 40 μm or more), and preferably 60 μm or less (e.g., 50 μm or less, typically 45 μm or less).
[0084] <Adhesive sheet thickness> The total thickness of the PSA sheet disclosed herein (including the thickness of the PSA layer and the substrate, but excluding the thickness of the release liner) is not particularly limited, and from the viewpoints of thinning, weight reduction, resource conservation, etc., it is preferably about 1000 μm or less (e.g., 500 μm or less, typically 300 μm or less), and may be 150 μm or less. Furthermore, from the viewpoint of ensuring good adhesive properties, etc., it is appropriate to make it 50 μm or more (e.g., 70 μm or more, typically 100 μm or more).
[0085] <Release liner> The release liner can be any conventional release paper, and is not particularly limited. For example, a release liner having a release treatment layer on the surface of a substrate such as a plastic film or paper, or a release liner made of a low-adhesion material such as a fluorine-based polymer (e.g., polytetrafluoroethylene) or a polyolefin-based resin (e.g., polyethylene, polypropylene), can be used. The release treatment layer can be formed by surface-treating the substrate with a release treatment agent such as a silicone-based, long-chain alkyl-based, fluorine-based, or molybdenum sulfide-based agent.
[0086] <Characteristics of adhesive sheets> The PSA sheet disclosed herein preferably has an adhesive strength to flexible urethane foam (adhesive strength to foam) of 3 N / 10 mm or more, measured at a tension rate of 300 mm / min and a peel angle of 180° under conditions of 23°C and 50% RH. Because the foam surface is rough, a PSA sheet exhibiting the above adhesive strength to foam can exhibit sufficient adhesion to rough surfaces. From the viewpoint of rough surface adhesion, the adhesive strength to foam is more preferably 4 N / 10 mm or more, even more preferably 5 N / 10 mm or more, and particularly preferably 6 N / 10 mm or more. The upper limit of the adhesive strength to foam is not particularly limited, and may be, for example, approximately 10 N / 10 mm or less. The adhesive strength to foam is measured in accordance with JIS Z 0237 by pressing a 2 kg roller back and forth against the surface of flexible urethane foam as an adherend, allowing it to stand for 30 minutes, and then measuring the adhesive strength at a tension rate of 300 mm / min and a peel angle of 180°. The adherend (flexible urethane foam) used is Color Foam (trade name "ECS" (gray)) manufactured by Inoac Corporation or an equivalent product. The flexible urethane foam (trade name "ECS" (gray)) has a density of 22±2 kg / m 3 The adhesive strength to the foam is measured by the method described in the Examples below.
[0087] The pressure-sensitive adhesive sheet disclosed herein preferably does not fall in a holding power test on a stainless steel plate measured under the following conditions: a temperature of 70°C, an application area of 10 mm x 30 mm, a load of 500 g, and a holding time of 1 hour. Pressure-sensitive adhesive sheets that satisfy these characteristics have excellent high-temperature holding power, and are less likely to peel or slip even when used in an embodiment exposed to high temperatures, making it easy to achieve excellent adhesive reliability. In some embodiments, the pressure-sensitive adhesive sheet preferably exhibits a displacement distance from the initial position in the holding power test of 3 mm or less, more preferably 2 mm or less, and even more preferably 1.5 mm or less. The holding power test is specifically carried out by the method described in the Examples below.
[0088] In some embodiments, the pressure-sensitive adhesive sheet preferably exhibits a peel distance of 5 mm or less both initially and after an aging test in a constant-load peel test measured by the method described in the Examples below. A pressure-sensitive adhesive sheet that satisfies these characteristics has sufficient resistance to continuous peel load even when stored for a long period of time, and can therefore achieve bonding and fixation with high adhesive reliability. The peel distance in the constant-load peel test is more preferably 3 mm or less, even more preferably 2 mm or less, and particularly preferably 1 mm or less (e.g., 0.5 mm or less).
[0089] Furthermore, the pressure-sensitive adhesive sheet disclosed herein preferably exhibits a rate of decrease in constant-load peel properties after an aging test (decrease rate after aging test) of 50% or less, as determined by the method described in the Examples below. Pressure-sensitive adhesive sheets that satisfy the above properties have excellent long-term quality stability and sufficient storage stability. It is particularly preferred that the pressure-sensitive adhesive sheet disclosed herein exhibits a rate of decrease after the aging test of 20% or less.
[0090] <Application> The adhesive composition or adhesive sheet disclosed herein is useful for joining components in various office automation equipment (e.g., PCs), home appliances (e.g., rice cookers, refrigerators), automobiles, building materials (e.g., housing construction materials), etc. (e.g., for fixing various parts in such products). [Example]
[0091] Several examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples. In the following description, "parts" and "%" are by weight unless otherwise specified. Furthermore, the amount of each material used is based on the amount excluding the solvent unless otherwise specified.
[0092] Example 1 (Preparation of Pressure-Sensitive Adhesive Composition) A pressure-sensitive adhesive composition with a NV of 50% was prepared by stirring and mixing 100 parts of a styrene-isoprene block copolymer (manufactured by Zeon Corporation, product name "Quintac 3520," styrene content 15%, diblock ratio 78%), 60 parts of a terpene resin (manufactured by Yasuhara Chemical Co., Ltd., product name "YS Resin PX1150N") as a natural product-based tackifier resin (A1), 20 parts of a rosin-based resin (manufactured by Arakawa Chemical Industries, Ltd., product name "Pensel D160") as a natural product-based tackifier resin (A2), 5 parts of a styrene-based resin (manufactured by Kraton Corporation, product name "SA140") as a petroleum-based tackifier resin (B), 10 parts of a liquid terpene resin (manufactured by Yasuhara Chemical Co., Ltd., product name "YS Resin PX300N") as a softener (C), 3 parts of an antioxidant, and toluene as a solvent. The antioxidant used was BASF's product name "IRGANOX CB612" (a blend of BASF's product names "IRGAFOS 168" and "IRGANOX 565" in a ratio of 2:1).
[0093] (Preparation of adhesive sheet) The pressure-sensitive adhesive composition was applied to the release-treated surface of a 75 μm-thick PET film treated with a silicone-based release agent, and dried at 120° C. for 3 minutes to form a 70 μm-thick pressure-sensitive adhesive layer. A release liner that had been release-treated with a silicone-based release agent was attached to the surface of the pressure-sensitive adhesive layer. In this way, a pressure-sensitive adhesive sheet (substrate-less double-sided pressure-sensitive adhesive sheet with a release liner) according to this example was produced.
[0094] <Examples 2 to 10 and Comparative Examples 1 to 12> The adhesive compositions of each example were prepared in the same manner as in Example 1, except that the type and amount of tackifier resin and the type and amount of softener were changed as shown in Tables 1 and 2, and adhesive sheets of each example were produced in the same manner as in Example 1 using each adhesive composition.
[0095] The materials used in the table are as follows: (Natural product-based tackifying resin that does not contain aromatic rings) "PX1150N": Yasuhara Chemical's product name "YS Resin PX1150N", a terpene resin with a softening point of 115°C "PX1000": Yasuhara Chemical Co., Ltd.'s product name "YS Resin PX1000", a terpene resin with a softening point of 100°C "PX800": Yasuhara Chemical Co., Ltd.'s product name "YS Resin PX800", a terpene resin with a softening point of 80°C "D160": Arakawa Chemical Industries' product name "Pensel D160", a rosin-based resin with a softening point of 157°C "A115": Arakawa Chemical Industries' product name "Super Ester A115", a rosin-based resin with a softening point of 120°C "A75": Arakawa Chemical Industries' product name "Super Ester A75", a rosin-based resin with a softening point of 80°C (petroleum-based tackifying resin containing aromatic rings) "SA140": Kraton's product name "SA140", a styrene-based resin with a softening point of 137°C "Kristalex 5140": Eastman Chemical Company's product name "Kristalex 5140", an aromatic petroleum resin with a softening point of 140°C "Neopolymer 150": JXTG Energy Corporation's product name "Nippon Oil Neopolymer 150", an aromatic petroleum resin with a softening point of 155°C "FTR2120": Mitsui Chemicals' product name "FTR2120", an aromatic petroleum resin with a softening point of 125°C "SX100": Yasuhara Chemical Co., Ltd. product name "YS Resin SX100", a styrene-based resin with a softening point of 100°C (Natural product-based tackifying resin containing aromatic rings) "T145": Yasuhara Chemical Co., Ltd. product name "YS Polyster T145", a terpene phenol resin with a softening point of 145°C "TO105": Yasuhara Chemical Co., Ltd.'s product name "YS Resin TO105", an aromatic modified terpene resin with a softening point of 100°C (Alicyclic / aliphatic petroleum resin) "M100": Arakawa Chemical Industries' product name "Arcon M100", an alicyclic petroleum resin with a softening point of 100°C "P100": Arakawa Chemical Industries' product name "Arcon P100", an aliphatic petroleum resin with a softening point of 100°C (softener) "PX300N": Yasuhara Chemical Co., Ltd.'s product name "YS Resin PX300N", a liquid terpene resin with a softening point of 30°C "PW-90": Idemitsu Kosan's product name "Diana Process Oil PW-90", a paraffin-based oil
[0096] <Evaluation method> (adhesion to foam) The release liner covering one adhesive side of the pressure-sensitive adhesive sheet (double-sided pressure-sensitive adhesive sheet) was peeled off, and the sheet was attached to a 50 μm thick PET film as a backing. This backed pressure-sensitive adhesive sheet was cut to a size of 10 mm wide and 100 mm long to prepare a test piece. The adherend was a 10 mm thick flexible urethane foam (Color Foam (trade name "ECS" (gray) manufactured by Inoac Corporation) cut to a width of 30 mm and a length of 100 mm. The other adhesive side of the test piece (the surface to be measured) was exposed at 23°C and 50% RH, and the exposed adhesive side of the test piece was pressed against the surface of the adherend by rolling a 2 kg roller back and forth once. After leaving the test piece in the same environment for 30 minutes, the 180° peel adhesion (adhesion to foam) [N / 10 mm] was measured at a pulling rate of 300 mm / min using a tensile tester in accordance with JIS Z 0237. An adhesion to foam of 3.0 N / 10 mm or more was considered to have sufficient rough surface adhesion. When measurements are carried out using a single-sided PSA sheet as a test piece, the PET film backing is not essential.
[0097] (70℃ holding power) The release liner covering one adhesive surface of a pressure-sensitive adhesive sheet (double-sided pressure-sensitive adhesive sheet) was peeled off and attached to a 50 μm-thick PET film for backing. This backed pressure-sensitive adhesive sheet was cut into 10 mm-wide strips to prepare test specimens. The other adhesive surface (surface to be measured) of the test specimen was exposed in an environment of 23°C and 50% RH, and the exposed adhesive surface of the test specimen was pressed against a stainless steel plate (SUS304) as an adherend, with a 10 mm wide, 30 mm long adhesion area, by rolling a 2 kg roller back and forth once. The test specimen thus attached to the adherend was left in the same environment for 30 minutes, after which the adherend was hung so that the length direction of the test specimen was vertical, and a 500 g load was applied to the free end of the test specimen. According to JIS Z 0237, the test specimen was left in an environment of 70°C with the load applied for 1 hour. After leaving the test piece, the distance (displacement distance) [mm] that it had shifted from the initial application position was measured. Measurements were conducted using three test pieces for each pressure-sensitive adhesive sheet (i.e., n=3), and the arithmetic mean value of the displacement distances [mm] for those test pieces was taken as the "70°C holding power." If even one test piece fell, it was recorded as "fell." If the test piece did not fall for one hour in the 70°C holding power test, it was determined to have sufficient high-temperature holding power. When measurements are carried out using a single-sided PSA sheet as a test piece, the PET film backing is not essential.
[0098] (Constant load peel test) Referring to FIG. 4, one adhesive surface 5A of a pressure-sensitive adhesive sheet (double-sided pressure-sensitive adhesive sheet) 5 before (initial) and after the aging test described below was attached to a 75 μm-thick PET film 52 for backing. This backed pressure-sensitive adhesive sheet 5 was cut to a size of 10 mm wide and 100 mm long to prepare a test piece 54. Under an environment of 23°C and 50% RH, the other adhesive surface 5B of test piece 54 was pressed against the surface of an adherend 56 by rolling a 2 kg roller back and forth once. This was left under the same environment for 30 minutes. A stainless steel plate (SUS304) was used as the adherend. Then, under an environment of 23°C and 50% RH, the adherend 56 was held horizontally with the surface to which the test piece 54 was attached facing downward, as shown in FIG. 4. A load 58 of 100 g (1.0 N) was applied to one end of the test piece 54 so that the peel angle was 90 degrees, and the peel distance [mm] after 24 hours was measured. Measurements were performed using two test pieces for each PSA sheet before (initial) and after the aging test (i.e., n=2), and the arithmetic mean value of the peel distance [mm] for those test pieces was used as the evaluation result for "constant load peel." If even one test piece fell, it was recorded as "dropped." When measurements are carried out using a single-sided PSA sheet as a test piece, the PET film backing is not essential.
[0099] (Aging test) The PSA sheet, together with the release liner covering the adhesive surface, was cut into a rectangular shape measuring 30 cm in length and 20 cm in width to prepare a sample for the aging test. The sample was stored for 10 days in an air-conditioned dryer maintained at 85°C. The samples were stored in the dryer in a hanging state, without overlapping each other.
[0100] (Storability) The shelf life was evaluated based on the peel distance [mm] measured in the constant load peel test for the pressure-sensitive adhesive sheet before and after the aging test. Specifically, from the results of the constant load peel test, the rate of decrease in the constant load peel property after the aging test (decrease rate after aging test) was calculated using the formula: Decrease rate after aging test [%] = (peel distance after aging test - peel distance before aging test) / peel distance before aging test × 100; I asked for more. If the rate of decrease after the aging test is 50% or less, it is judged to have sufficient shelf life, and if the rate of decrease after the aging test is 20% or less, it is judged to have excellent shelf life.
[0101] The outline of each example and the evaluation results are shown in Tables 1 and 2.
[0102] [Table 1]
[0103] [Table 2]
[0104] As shown in Tables 1 and 2, the PSA sheets of Examples 1 to 10 had foam adhesive strength of 3.0 N / 10 mm or more, did not fall in the 70°C holding strength test, and showed a constant load peel property decrease rate of 50% or less after the aging test, and all had sufficient rough surface adhesion, high temperature holding strength, and storage stability. On the other hand, Comparative Examples 1 to 12 were inferior in at least one of foam adhesive strength, 70°C holding strength, and storage stability.
[0105] Specifically, Examples 1 and 2 are the results of examining the content of an aromatic petroleum-based tackifying resin (B) having a softening point of over 100°C. A comparison of the results of Example 1 with those of Comparative Examples 6 and 8, which did not use tackifying resin (B), reveals that rough surface adhesion and high-temperature holding power can be improved by increasing the content of tackifying resin (B) to 5 parts or more. A comparison of the results of Example 2 with those of Comparative Examples 9 and 10 reveals that excellent rough surface adhesion can be obtained by increasing the content of tackifying resin (B) to 40 parts by weight or less. Comparative Example 6 mimics the composition of Example 8 in Patent Document 1, and Comparative Example 8 mimics the composition of Example 2 in Patent Document 2. Comparative Example 7 mimics the composition of Example 2 in Patent Document 3. Comparative Example 9 is an example in which the amount of aromatic petroleum resin (B) was increased from the composition of Example 4, and Comparative Example 10 is an example in which the amount of aromatic petroleum resin (B) was increased from the composition of Example 3.
[0106] Furthermore, a comparison of the results of Examples 3 and 4 with the results of Comparative Examples 9, 11, and 12 reveals that sufficient rough surface adhesion can be achieved when the content of the natural product-based tackifier resin (A) is within the range of 40 to 120 parts and the total amount of tackifier resin is within the range of 60 to 160 parts. Furthermore, the results of Comparative Example 11 reveal that if the content of the natural product-based tackifier resin (A) is too high, the high-temperature holding power decreases. Note that Comparative Example 11 is an example in which the amount of the natural product-based tackifier resin (A) is increased from the composition of Example 10, and Comparative Example 12 is an example in which the amount of the natural product-based tackifier resin (A) is decreased from the composition of Example 2.
[0107] Examples 5-6 and Comparative Example 5 are the results of investigating the softening point of the aromatic petroleum-based tackifier resin (B). Comparison of these results shows that a softening point of the aromatic petroleum-based tackifier resin (B) exceeding 100°C improves high-temperature retention. Examples 7-8 and Comparative Example 4 are the results of investigating the softening point of the natural product-based tackifier resin (A). It is found that using a natural product-based tackifier resin (A) with a softening point exceeding 80°C can achieve both rough surface adhesion and high-temperature retention. Examples 9-10 and Comparative Examples 1-2 are the results of investigating the amount of softener. It is found that using a softener in an amount ranging from 5 to 40 parts can achieve both rough surface adhesion and high-temperature retention. Comparative Example 5 is an example in which the aromatic petroleum-based tackifier resin (B) in the composition of Example 2 is replaced with one having a lower softening point. Comparative Example 4 is an example in which the natural product-based tackifier resin (A) in the composition of Example 5 is replaced with one having a lower softening point. Comparative Examples 1 and 2 are examples in which the amount of softener used was changed from the composition of Example 2.
[0108] In Comparative Example 3, although the results of the initial constant load peel test were good, the constant load peel property after the aging test deteriorated and storage stability was not obtained. Comparative Example 3 is an example in which a terpene phenol resin was used instead of the natural product-based tackifier resin (A) in the composition of Example 7, and this is thought to be because the use of the terpene phenol resin caused the adhesive to deteriorate.
[0109] The above results demonstrate that a pressure-sensitive adhesive composition containing a block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound, a tackifier resin, and a softener, comprising a natural product-based tackifier resin (A) having a softening point above 80°C and not containing an aromatic ring, and a petroleum-based tackifier resin (B) having a softening point above 100°C and containing an aromatic ring, wherein the content of tackifier resin (A) is 40 to 120 parts by weight per 100 parts by weight of the block copolymer, the content of tackifier resin (B) is 5 to 40 parts by weight per 100 parts by weight of the block copolymer, the total amount of tackifier resin is 60 to 160 parts by weight per 100 parts by weight of the block copolymer, and the content of softener is 5 to 40 parts by weight per 100 parts by weight of the block copolymer, can form a pressure-sensitive adhesive that combines rough surface adhesion and high-temperature holding power and has good storage stability.
[0110] Although specific examples of the present invention have been described above in detail, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and alterations of the specific examples exemplified above. [Explanation of symbols]
[0111] 1,2,3 Adhesive sheet 11 First adhesive layer 12 Second adhesive layer 15 Base material 21,22 Release liner
Claims
1. The composition contains a block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound, a tackifier resin, and a softener, The tackifier resin is A natural product-based tackifier resin (A) having a softening point of more than 80° C. and not containing an aromatic ring; A petroleum-based tackifier resin (B) having a softening point exceeding 100°C and containing an aromatic ring; Including, the content of the tackifier resin (A) is 40 to 120 parts by weight based on 100 parts by weight of the block copolymer, the content of the tackifier resin (B) is 5 to 40 parts by weight based on 100 parts by weight of the block copolymer, the total amount of the tackifier resin is 60 to 160 parts by weight based on 100 parts by weight of the block copolymer; The pressure-sensitive adhesive composition, wherein the content of the softener is 5 to 40 parts by weight based on 100 parts by weight of the block copolymer.
2. The pressure-sensitive adhesive composition according to claim 1 , wherein the tackifier resin (A) comprises a terpene resin as a tackifier resin (A1) and a rosin-based resin as a tackifier resin (A2).
3. The pressure-sensitive adhesive composition according to claim 2 , wherein the tackifier resin (A2) contains a rosin-based resin having a softening point of 150° C. or higher.
4. The pressure-sensitive adhesive composition according to any one of claims 1 to 3, wherein the content of the phenolic tackifier resin is less than 1 part by weight based on 100 parts by weight of the block copolymer.
5. The pressure-sensitive adhesive composition according to any one of claims 1 to 3, wherein the block copolymer is a styrene-based block copolymer.
6. The pressure-sensitive adhesive composition according to any one of claims 1 to 3, wherein the block copolymer is a styrene-isoprene block copolymer.
7. The pressure-sensitive adhesive composition according to claim 5, wherein the styrene-based block copolymer has a styrene content of 10 to 22 wt %.
8. A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to any one of claims 1 to 3.
9. A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer, The pressure-sensitive adhesive layer contains a block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound, and a tackifier resin, the content of the phenol-based tackifier resin in the pressure-sensitive adhesive layer is less than 1 part by weight based on 100 parts by weight of the block copolymer; The pressure-sensitive adhesive sheet has the following properties: The adhesive strength to a soft urethane foam is 3 N / 10 mm or more when measured under conditions of a tensile speed of 300 mm / min and a peel angle of 180 degrees in an environment of 23° C. and 50% RH; and Does not fall in a holding strength test against a stainless steel plate measured under the conditions of a temperature of 70°C, an application area of 10 mm x 30 mm, a load of 500 g, and a holding time of 1 hour; An adhesive sheet that satisfies the above.